2012
DOI: 10.1093/aob/mcs008
|View full text |Cite
|
Sign up to set email alerts
|

Virus-induced gene silencing (VIGS) in Cysticapnos vesicaria, a zygomorphic-flowered Papaveraceae (Ranunculales, basal eudicots)

Abstract: The high penetrance, severity and stability of pTRV-mediated silencing, including the induction of meristem-related phenotypes, make C. vesicaria a very promising new focus species for evolutionary-developmental (evo-devo) studies in the Papaveraceae. This now enables comparative studies of flower symmetry, inflorescence determinacy and other traits that diversified in the Papaveraceae.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 54 publications
2
17
0
Order By: Relevance
“…Similar evolutionary changes are reported in comparisons of whole transcriptional programmes in floral organs [20,85,87,88]. Much progress has been made in our understanding of floral developmental genetics in Ranunculales [78,[89][90][91][92][93][94], but the basal eudicot grade has not been representatively studied to date. The available data suggest that genetic programmes for floral organ identity are often more broadly deployed in the flowers of non-Pentapetalae angiosperms than in the flowers of Pentapetalae.…”
Section: Genetic Origin Of the Pentapetalae Flowersupporting
confidence: 58%
“…Similar evolutionary changes are reported in comparisons of whole transcriptional programmes in floral organs [20,85,87,88]. Much progress has been made in our understanding of floral developmental genetics in Ranunculales [78,[89][90][91][92][93][94], but the basal eudicot grade has not been representatively studied to date. The available data suggest that genetic programmes for floral organ identity are often more broadly deployed in the flowers of non-Pentapetalae angiosperms than in the flowers of Pentapetalae.…”
Section: Genetic Origin Of the Pentapetalae Flowersupporting
confidence: 58%
“…() for E. californica and in Hidalgo et al . () for C. vesicaria . Signals were recorded using a Leitz Laborlux S microscope equipped with a Leica DFC420 C digital camera (Wetzlar, Germany).…”
Section: Methodsmentioning
confidence: 97%
“…Ranunculales include several model species that are susceptible to functional genetics by virus-induced gene silencing (VIGS). Among these are the Papaveraceae representatives Papaver somniferum (Hileman et al, 2005), Eschscholzia californica (Wege et al, 2007) and Cysticapnos vesicaria (Hidalgo et al, 2012), and, in Ranunculaceae, Aquilegia coerulea (Gould & Kramer, 2007), Thalictrum ssp. (Di Stilio et al, 2010) and Nigella damascena (Gonc ßalves et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…They have found that silencing of LAP profoundly increased the larval mass of Manduca sexta which fed on silenced plants demonstrating its involvement in defensive function against herbivores [4]. Agrobacterium tumefaciens mediated transfer of CvPDS gene (Phytoene desaturase) and CvFLOgene (Floricaula) into Cysticapnos vesicaria (Papaveraceae, basal eudicots) through Tobacco rattle virus (TRV)-based vectors have resulted in strong photobleaching of green parts and reduction of endogenous CvPDS transcript levels and affected floral phyllotaxis, symmetry and floral organ identities respectively [5]. Glutathione S-transferase (GST) was known to be up-regulated during the infection of fungal pathogen O. neolycopersici in resistant tomato plants (Solanum habrochiates G1.1560) that resulted in the accumulation of H 2 O 2 and Hypersensitive reaction (HR) and retarded the growth of the pathogen.…”
Section: Recent Advances On Vigs In Plant Functional Studymentioning
confidence: 99%